The usage of social media, social networking sites and students’ ethics: a study of students at Universiti Malaysia Sabah Labuan International Campus - Azizan Had; Starry Garijih (2016)
The research tries to answer the question on what were the reasons the social media and networking sites were used by students? Which particular component of the social media is the main component of their usage? Is it merely as a means of pastime activity, a source of showing affection to another (friends, colleagues, parents, etc.), source of trends (fashion), sharing problems or social networking. Do students understand the ethics of using the social media? This is what is focused in this article where a quantitative survey was used to determine a students’ response on their usage of the social media and social networking websites. The findings show that the main reason students used the social media and networking websites is purely for academic (learning) purpose. Students also used it as a means of entertainment and enjoyment during pastime.